Characterization and antibiotic resistance of E. coli recovered from healthy captive Non – human Primates in Nigeria. (African Journal of Biomedical Research, 2022)
Escherichia coli is one of the members of the family Enterobacteriacea. The cells appear rod like in shape and are Gram-negative bacteria. It is part of micro flora of animals with non-human primates (NHPs) inclusive. E. coli is pathogenic and is causal organism of diarrhea all over the world. The aims of this study are to determine whether non – human primates are reservoirs for E. coli, to investigate the relatedness of E. coli with others in some regions and to determine the antibiotic sensitivity as well as resistance of the isolates. Escherichia coli were recovered from 5 (11%) out of the 43 NHPs. All the isolates appeared non- haemolytic. Findings of this study revealed that the isolates showed high level resistance to Amoxicillin/clavulanic (80%), Sulphamethoxazole/trimethoprim (80%), Gentamycin (60%), Cefoxitin (60%) and Ciprofloxacin (60%). Most of the isolates are multidrug resistant, showing resistance to two, three or more antibiotics. There are similar genetic backgrounds within E. coli isolates identified from Cercopithecus mona and Cercopithecus sebaeus. Clustering shows that isolates from Cercopithecus mona and Papio Anubis clustered together within the same clade.Wild monkeys usually interact with humans through activities such as domestication and tourism. Through these interactions, pathogenic bacteria are transmitted from humans and animals, particularly wild monkeys. This is a potential source of infections in man. Isolation of E. coli in this study shows that NHPs are natural reservoirs of the organisms, the isolates are genetically related to each other and are multidrug resistant.Keywords: E. coli, non- human primates, antibiotics resistance, sequence.